2019
DOI: 10.1177/1078155219887212
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab-induced thrombotic thrombocytopenic purpura

Abstract: Introduction Pembrolizumab is a humanised monoclonal antibody targeting the receptor programmed cell death protein-1 (PD-1), with anti-tumour activity demonstrated for many malignancies. Such immune checkpoint inhibitors are associated with many immune-related adverse events including rash, colitis, hepatitis, pneumonitis, endocrinopathy and, rarely, haematological adverse events, including immune-related thrombocytopenia. Cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Although ICIs have been approved for treating various types of human malignancies, immune-related thrombocytopenia is most likely to be reported in NSCLC ( 5 11 , 24 , 25 ), melanoma ( 12 20 ), lymphoma ( 21 ), pancreatic cancer ( 22 ), and renal cell carcinoma ( 23 ), which is consistent with retrospective data from multiple institutions ( 26 ). Previous case and retrospective studies show that immune thrombocytopenia occurred in cancer patients treated with PD-1 inhibitor monotherapy, such as nivolumab or pembrolizumab, or a CTLA-4 inhibitor, or a combination with PD-1 and a CTLA-4 inhibitor ( Table 1 ).…”
Section: Incidence and Onset Of Immune Thrombocytopenia Induced By Icsupporting
confidence: 74%
See 1 more Smart Citation
“…Although ICIs have been approved for treating various types of human malignancies, immune-related thrombocytopenia is most likely to be reported in NSCLC ( 5 11 , 24 , 25 ), melanoma ( 12 20 ), lymphoma ( 21 ), pancreatic cancer ( 22 ), and renal cell carcinoma ( 23 ), which is consistent with retrospective data from multiple institutions ( 26 ). Previous case and retrospective studies show that immune thrombocytopenia occurred in cancer patients treated with PD-1 inhibitor monotherapy, such as nivolumab or pembrolizumab, or a CTLA-4 inhibitor, or a combination with PD-1 and a CTLA-4 inhibitor ( Table 1 ).…”
Section: Incidence and Onset Of Immune Thrombocytopenia Induced By Icsupporting
confidence: 74%
“…An increased number of cases of hematologic disorders have been reported since 2017, which may be attributed to increased application of ICIs and improved recognition of adverse effects ( 4 ). In particular, immune thrombocytopenia induced by ICIs has been reported in a few NSCLC, melanoma, and other malignancies ( 5 25 ). We herein describe one case of immune thrombocytopenia induced by the PD-L1 inhibitor durvalumab and its clinical management.…”
Section: Introductionmentioning
confidence: 99%
“…As in our patient's case, ADAMTS 13 inactivation is frequently caused by the presence of an inhibitor, which in most cases is related to autoimmunity and associated autoantibodies [14]. TTP as an irAE from ICIs is a rare clinical complication that has not been discussed in comprehensive reviews of hematologic irAEs [6–10], with only three prior cases reported to date [11–13] (Table 2). Given the high fatality rate if plasma exchange is delayed, TTP must be included in the differential diagnosis for thrombocytopenia and hemolytic anemia of patients with cancer receiving immunotherapy, as early detection and treatment are critical to prevent morbidity and mortality.…”
Section: Discussionmentioning
confidence: 89%
“…It has been reported that anti–CTLA‐4 agents are more toxic than anti–PD‐1 therapy [4], and retrospective reviews showed higher incidence of immune‐related fatalities with the former [5]. In addition, single‐agent pembrolizumab was also recently reported to be associated with TTP in a patient with metastatic non‐small cell lung cancer [13]. Nivolumab is associated with a wide variety of hematologic irAEs, but to our knowledge, this is the first report of immunotherapy‐induced TTP from single‐agent nivolumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation